APLIKASI OTOMATISASI PENGENDALIAN KADAR AIR PADA TANAMAN TAMAN KOTA MENGGUNAKAN ARDUINOPADA KANTOR DINAS LINGKUNGAN HIDUP - Mubarok, Husni; -, Afrizal (JURNAL AKADEMIKA, 2020)
Plant watering automation system is one of the watering techniques that uses tools that have been designed in such a way as to work to do watering automatically. This system has also been embedded in coding to read the condition of the soil around the plant as a reference for watering how much water is released by the hose to water the plants. The research was conducted at the Office of the Environmental Office of Jambi City. The procedure for making this tool is started with the calibration tool, system design tool, planting coding on the tool, and testing the performance of the tool and testing on the machine. The results showed that the design of the plant watering automation system was realized based on the moisture content of the plant, the water content control value for the water pump to live at <10% and the pump would die at > 40%. from a more efficient and precise watering test.